Poor Man’s Cell-block Preparation, a Novel Idea which Can be Applied to Basic Health Care Facilities in Resource-poor Settings - Saleem, Huzaifa; Javed, Mehwish; Saleem, Aniqua; Atif, Sadia; Rafi, Rabia (Asian Pacific Journal of Cancer Biology, 2021)
Objective: To determine the diagnostic yield of cell blocks, prepared by the vapour fixation method, using laboratory supplies easily available at any low resource laboratory setup or outpatient department of a basic healthcare unit. Methods: Prospective descriptive study was carried out at Healthways Laboratories Rawalpindi, for 6 months from 1st January 2017 to 30th June 2017. Walk in patients referred to the lab for FNAC were selected by non probability convenient sampling. After preparing FNAC slides from first pass, the patients were briefed about the cell block material and after informed consent second dedicated passes were done to make cell blocks. Results: Out of 47 cases, there were 25 (53.2 %) breast lumps, 8 (17%) superficial collections, 7 (15.1%) lymphadenopathies, 6 (12.8%) thyroid swellings and 1 salivary gland swelling. Technique yielded moderate to high cellularity in 33 (70.2%) cases, 16 from malignant and 1 from benign breast lumps, 5 from thyroid, 3 from reactive and 3 from metastatic lymphnodes, 3 from abscesses, 1 from lipoma and 1 from salivary gland. Low cellularity 14 (29.8%) cases were from 5 benign and 3 malignant breast lumps, 2 hematomas and 1 case each from thyroid, metastatic lymphnode, abscess and lipoma. Good cellularity was achieved in 16 (84.2%) of 19 cases of malignant breast lesions, 3 (15.8%) were hypo cellular of which 1 was non-diagnostic on FNAC smear. Cell block diagnosis was comparable to FNAC in 35 of 47 (74.4%) cases. Non diagnostic cases on cell block were more, 13 versus 3 cases on FNAC. The kappa value of agreement in diagnosis was 0.64. Conclusions: Poor man’s cell block method is simplest and effective method of cell block preparation which must be advocated at basic healthcare units and low tech laboratory. Its diagnostic potential must be further explored.